2016
DOI: 10.1590/0103-6440201600735
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Cytotoxicity, pH and Dissolution Rate of AH Plus and MTA Fillapex

Abstract: The aim of the present study was to verify the long-term cytotoxic effects of the MTA Fillapex and to compare them with AH Plus. Dissolution rate and pH were also evaluated. Human osteoblast cells were incubated with elutes of fresh specimens from AH Plus and MTA Fillapex, and with elutes of the same specimens for 4 successive weeks. Elute's pH was evaluated at each time point. A multiparametric cell viability assay was performed. For dissolution rate, ISO methodology was used. The results were analyzed by one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
32
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 20 publications
6
32
0
3
Order By: Relevance
“…Such higher solubility might lead to sealer particles release, creating gaps and failures in sealer/root canal walls interface, allowing microleakage of fluids and microrganisms within the root canal system. 27 Despite the lower levels of coronal microleakage at the 15-day period, the results for Sealapex were statistically similar to MTA Fillapex at both periods of analysis. Calcium hydroxide-based root canal sealers, as Sealapex, are used in endodontic therapy to improve apical repair, as they release calcium ions and promote deposition of mineralized tissue at their site of action.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Such higher solubility might lead to sealer particles release, creating gaps and failures in sealer/root canal walls interface, allowing microleakage of fluids and microrganisms within the root canal system. 27 Despite the lower levels of coronal microleakage at the 15-day period, the results for Sealapex were statistically similar to MTA Fillapex at both periods of analysis. Calcium hydroxide-based root canal sealers, as Sealapex, are used in endodontic therapy to improve apical repair, as they release calcium ions and promote deposition of mineralized tissue at their site of action.…”
Section: Discussionmentioning
confidence: 72%
“…26,27 This root canal sealer presented a solubility higher than 3%, which is not in accordance with the Specification N.º 57 of the ANSI/ADA, 24 compromising other physico-chemical properties, as sealing ability. Such higher solubility might lead to sealer particles release, creating gaps and failures in sealer/root canal walls interface, allowing microleakage of fluids and microrganisms within the root canal system.…”
Section: Discussionmentioning
confidence: 89%
“…In a four-week study, MTA Fillapex showed continual cytotoxicity. 29,259 Similarly, iRoot SP showed continual cytotoxicity in a six-week study. 233 Both MTA sealers were more cytotoxic than AH Plus over the same testing period.…”
Section: Cytotoxicity (Iso 10993-3)mentioning
confidence: 91%
“…259 An alternative method would be to place freshly mixed MTA immediately into a simulated root-end filling that is then exposed to the testing culture. 257 This prevents the disintegration of the MTA.…”
Section: Compressive Strength (Iso 9917-1)mentioning
confidence: 99%
See 1 more Smart Citation